Perbandingan Kinerja Antara Gatling dan Apache JMeter pada Uji Beban RESTful API - Abda'u, Prih Diantono; Susanto, Agus; Supriyono, Abdul Rohman; Prasetyanti, Dwi Novia (Infotekmesin, 2024)
This research explores and compares the performance of two popular load testing tools, namely Gatling and Apache JMeter, with a focus on API performance testing. The rapid growth in web and mobile application development highlights the urgent need to ensure optimal API performance. This research was conducted to provide in-depth insight into the advantages and disadvantages of these two testing tools through the use of similar testing scenarios. The experimental method involves implementing test scenarios that include load variations and high demands on both devices. The main parameters observed include API response time, throughput, and latency. In-depth analysis was carried out on the data obtained to evaluate the reliability and efficiency of each tool. The results of this research provide a comprehensive understanding of the performance of Gatling and Apache JMeter in the context of API performance testing. These findings can provide practical guidance for software developers and testing practitioners in selecting load testing tools that suit their project needs. Recommendations for future research include expanding exploration of other load testing tools, comparison with more complex test scenarios, and integration with performance monitoring tools for more holistic analysis. Thus, this research is expected to make a significant contribution to the understanding and selection of effective load testing tools in web and mobile application development.